Doświadczenia nad Parciem Geostatycznym - Haberzak, A. (Engineering Transactions, 1958)
Geodynamic and geostatic pressure are two forms of soil pressure constituting the external load of retaining walls. The first takes place when the structure starts being deformed or moving in the direction of soil mass outside the structure; the second when the both structure and soil are at rest. Analysis and experiments show that geostatic pressure is higher than the geodynamic pressure. In consequence it should be considered in calculating retaining structures.However, the calculation of geostatic pressure presents considerable difficulties, the methods of structural mechanics being not adequate for determining the directions and the distribution of the stresses in soil at rest. Therefore, all theoretical considerations aiming at the computation of the geostatic soil pressure should necessarily be based on more or less justified hypotheses. The magnitudes of geostatic pressure approaching in an adequate manner the real values should therefore be sought by experimental methods. The idea of the apparatus designed by the author is based on the utilization of the friction force during slip. On the basis of results of measurements of the drag during the process of drawing of elastic bands at various levels of the front wall of a box filled up with sand, unit pressures were calculated, and hence the horizontal component of the total pressure. On the same basis, using a suitble support and a suitable connection between the front wall and the side walls, the vertical component was also determined, and then theresultant pressure.The sand used was river sand of specific weight 1650 kG/m3, the box being filled to three different depths: 50, 70 and 95 cm. The differences between the horizontal components of geostatic pressure, found experimentally, and geodynamic pressure, calculated by the Coulombian method assuming that the soil-to-soil and soil-to-structure friction angle are equal to Yz = 32° and Vm = 0° respectively, range for loose sand, within the limits of 12% to 23 and decrease with decreasing depth of the sand layer. The vertical components remain practically unchanged. The graphs of unit pressures have a slightly convex form. The measurements for rammed sand show an increase in the horizontal component up to 100%, the vertical component remaining unchanged. In the latter case, it was found moreover that if the soil mass rests on a rigid foundation, the maximum soil pressure will appear just above the lower edge of the retaining wall.